THE RELATIONSHIP OF PHYSICO-CHEMICAL PROPERTIES AND ACTIONS ON BIOLOGICAL OBJECTS OF ARTESIAN WATER WITH GAS NANOBUBBLES (Ar, O2) - O. M, Kanunnikova; A.V, Trubachev; V. I, Kozhevnikov; V.VАksenova; T.N, Kropacheva; A.A, Solovyov (IJRDO-Journal of Applied Science, 2017)
It is established that the physico-chemical properties of gas saturated artesian water in the electromagnetic field change non-monotonic with increasing saturation time. It is shown that in areas with minimal coefficients of expansion and extremums of the viscosity the highest biological activity of water containing nanopositive phase of argon and oxygen is occur. It is suggested that the cause of the biological activity of the treated water is the effect based on atomic and structural features of water molecules, and nanobubbles electric double layer formed in artesian water in the experiment